MONOCOT POLLEN FLORA OF PASCHIM MEDINIPUR DISTRICT, WEST BENGAL WITH A NOTE ON POLLEN DISPERSAL MECHANISM - Ghosh, Arundhati; Karmakar, Prakash (Current Botany, 2017)
During the present investigation pollen morphological studies of 66 species belonging to 19 families of monocots in Paschim Medinipur district have been worked out by light microscopy. The studied families are Agavaceae, Amaryllidaceae, Arecaceae, Asphodelaceae, Cannaceae, Colchicaceae, Commelinaceae, Costaceae, Cyperaceae, Hemerocallidaceae, Hydrocharitaceae, Iridaceae, Liliaceae, Limnocharitaceae, Musaceae, Poaceae, Pontederiaceae, Typhaceae and Zingiberaceae. The apertural patterns are mostly belong to two different categories viz. monosulcate form (Agavaceae, Amaryllidaceae, Arecaceae, Asphodelaceae, Colchicaceae, Commelinaceae, Costaceae, Hemerocallidaceae, Hydrocharitaceae, Iridaceae, Liliaceae, Limnocharitaceae, Musaceae, Poaceae, Pontederiaceae) and anaporate type (Cyperaceae, Poaceae and Typhaceae). The shape of the pollen grains with monosulcate apertures are mostly oblate to peroblate type whereas taxa showing anaporate apertures are more or less spheroidal. Regarding the mode of pollen dispersal plant taxa with monosulcate apertures and apiculate surface ornamentations (e.g., reticulate, rugulate, spinulate, verrucate) are entomophilous (mainly melittophilous) whilest anaporate with smooth or minutely apiculate surface features are anemophilous. Here, entomophilous taxa provide rewards as pollen grains and nectar to the honeybee speecies, therefore, contribute as resource mobilizer for sustainance of honeybee colonies.Â